Patient experiences of switching from Efavirenz- to Dolutegravir-based antiretroviral therapy: a qualitative study in Uganda - Adelline Twimukye (BMC, 2021)
Abstract Background In 2019, the World Health Organisation (WHO) recommended Dolutegravir (DTG) as the preferred first-line antiretroviral treatment (ART) for all persons with HIV. ART regimen switches may affect HIV treatment adherence. We sought to describe patient experiences switching from EFV to DTG-based ART in Kampala, Uganda. Methods Between July and September 2019, we purposively sampled adults living with HIV who had switched to DTG at the Infectious Diseases Institute HIV clinic. We conducted in-depth interviews with adults who switched to DTG, to explore their preparation to switch and experiences on DTG. Interviews were audio-recorded, transcribed and analysed thematically using Atlas ti version 8 software. Results We interviewed 25 adults: 18 (72%) were women, and the median age was 35 years (interquartile range [IQR] 30–40). Median length on ART before switching to DTG was 67 months (IQR 51–125). Duration on DTG after switching was 16 months (IQR 10–18). Participants reported accepting provider recommendations to switch to DTG mainly because they anticipated that swallowing a smaller pill once a day would be more convenient. While most participants initially felt uncertain about drug switching, their providers offer of frequent appointments and a toll-free number to call in the event of side effects allayed their anxiety. At the same time, participants said they felt rushed to switch to the new ART regimen considering that they had been on their previous regimen(s) for several years and the switch to DTG happened during a routine visit when they had expected their regular prescription. Some participants felt unprepared for new adverse events associated with DTG and for the abrupt change in treatment schedule. Most participants said they needed additional support from their health providers before and after switching to DTG. Conclusion and recommendations Adults living with HIV stable on an EFV-based regimen but were switched to DTG in a program-wide policy change found the duration between counselling and drug switching inadequate. DTG was nonetheless largely preferred because of the small pill size, once daily dosing, and absence of EFV-like side effects. Community-engaged research is needed to devise acceptable ways to prepare participants for switching ART at scale.